Metastatic Primary Testicular Neuroendocrine Carcinoma Associated with Somatic Malignant Transformation of Teratoma: A Rare Case Report - Jirapat Wonglhow; Patrapim Sunpaweravong; Chirawadee Sathitruangsak; Kanet Kanjanapradit; Arunee Dechaphunkul (Case Reports in Oncology, 2022)
Testicular neuroendocrine tumor associated with teratoma is a rare disease. Very few cases have been reported in the literature, particularly cases involving visceral metastasis. Teratoma with somatic malignant transformation (SMT) is associated with a worse prognosis compared to teratoma without SMT. Previous data have suggested that chemotherapy regimens should be directed toward the transformed histology; however, those suggestions were based on patients with rhabdomyosarcoma, adenocarcinoma, and primitive neuroectodermal subtypes. To the best of our knowledge, only 2 cases with visceral metastasis have been reported, and a better outcome with the bleomycin/etoposide/cisplatin regimen, which responds strongly to germ cell tumors, has been reported in these cases. In contrast, 2 others with lymph node metastasis did not respond to these regimens. Here, we report a case of a patient with testicular neuroendocrine carcinoma associated with teratoma who achieved a good response to chemotherapy.